Triple-negative ectopic breast cancer of the male scrotum: a case report - Nie, Yuhui; Song, Chen; Wang, Jingru; Wu, Kun; Yu, Mingxin; Shen, Xin; Bian, Yandong; Liu, Shuzhen (Frontiers in Oncology, 2024)
Male breast cancer represents only 1% of all breast malignancies, with ectopic breast cancer in men being even rarer and highly prone to diagnostic challenges. Extramammary Paget’s disease (EMPD), a rare cutaneous tumor with non-specific clinical symptoms, is susceptible to misdiagnosis. This report discusses the case of an older male patient who presented with a scrotal mass, later identified as ectopic breast invasive adenocarcinoma upon pathological examination post-lesion excision. Immunohistochemistry confirmed a triple-negative profile and EMPD diagnosis, with no malignancies detected in either breast. Despite multiple treatment regimens and recurrence following adjuvant chemotherapy, the disease progressed with associated chemotherapy-related side effects, resulting in a 25.5-month survival period. The scarcity of literature on male ectopic breast cancer complicates the understanding of its incidence and optimal treatment strategies, increasing the risk of misdiagnosis. This study highlights the diagnostic and therapeutic challenges of this rare case, emphasizing the need for early recognition of atypical manifestations. The manuscript aims to assist clinicians by sharing case-specific insights and reviewing pertinent literature to enhance comprehension and management of similarly rare cases.